ТӨЛӨӨЛЛИЙН ЗАСАГ, ТӨЛӨӨЛЛИЙН АРДЧИЛЛЫН ҮЗЭЛ САНАА БА МОНГОЛЫН АРДЧИЛАЛ: ТӨРИЙН БА УЛС ТӨРИЙН ИНСТИТУЦУУД ТӨЛӨӨЛЛИЙН АРДЧИЛАЛД ХЭРХЭН НӨЛӨӨЛЖ БАЙНА ВЭ?” - Ж.ТӨРТОГТОХ; С.МӨНХБАТ; Б.Эрдэнэдалай; Г.Туяагэрэл (Politology, 2023)
The key mechanisms and institutions to operate democracy are the keys to recognizing the quality of democracy. Each country has a variety of indicators that will help recognize the quality of democracy, such as ethics, law, equal and accessible participation of citizens. In studying the impact of the State Institution, the political institution, and other stakeholders involved in the strengthening of democracy, he analyzed factors and dependency tests and analyzed the challenges facing the strengthening of democracy.